Damaging effects of UVA, blue light, and infrared radiation: in vitro assessment on a reconstructed full-thickness human skin - Montero, Paula; Roger, Inés; Milara, Javier; Cortijo, Julio (Frontiers in Medicine, 2023)
Exposure to solar radiation can cause a range of skin damage, including sunburn, erythema, skin carcinogenesis, the release of reactive oxygen species (ROS), inflammation, DNA damage, and photoaging. Other wavelengths beyond UVB, such as UVA, blue light, and infrared radiation, can also contribute to the harmful effects of solar radiation. Reconstructed full-thickness human skin has the potential to serve as effective predictive in vitro tools for evaluating the effects of solar radiation on the skin. The aim of this work was to evaluate the damaging effects of UVA, blue light, and infrared radiation in a full-thickness skin model in terms of viability, inflammation, photoaging, tissue damage, photocarcinogenesis. Full thickness skin models were purchased from Henkel (Phenion FT; Düsseldorf, Germany), and irradiated with increasing doses of UVA, blue light, or infrared radiation. Different endpoints were analyzed on the tissues: Hematoxylin-eosin staining, inflammation mediators, photoaging-related dermal markers and oxidative stress marker GPX1, evaluated by real-time quantitative PCR, as well as photocarcinogenesis markers by Western Blot. The results showed differential responses in cytokine release for each light source. In terms of photoaging biomarkers, collagen, metalloproteinases 1 and 9, elastin, and decorin were modulated by UVA and blue light exposure, while not all these markers were affected by infrared radiation. Furthermore, exposure to UVA and blue light induced loss of fibroblasts and modulation of the photocarcinogenesis markers p53 and p21. In conclusion, the presented results suggest that the various wavelengths of solar light have distinct and differential damaging effects on the skin. Understanding the differential effects of UVA, blue light, and infrared radiation can serve as a valuable tool to investigate the efficacy of photoprotective agents in full thickness skin models.